2018
DOI: 10.1002/jlb.3a1017-398rr
|View full text |Cite
|
Sign up to set email alerts
|

β2-Adrenoceptors inhibit neutrophil extracellular traps in human polymorphonuclear leukocytes

Abstract: This study tests the hypothesis that in isolated human polymorphonuclear leukocytes (PMN) adrenergic ligands can affect neutrophil extracellular trap (NET) formation. We have previously shown that, in PMN, adrenaline (A), through the activation of adrenergic receptors (AR), reduces stimulus-dependent cell activation; we have, therefore, planned to investigate if AR are involved in NET production. PMN were obtained from venous blood of healthy subject. The ability of adrenergic ligands to affect reactive oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 48 publications
(139 reference statements)
0
10
0
Order By: Relevance
“…All patients received the same treatment doses: nebulized dornase alfa (2.5 mg) co-administered twice daily with the short-acting β 2 -agonist albuterol (2.5 mg, hereafter abbreviated as nDA+A) to improve delivery to the alveoli. Of note, β 2 -adrenoreceptor agonism may also inhibit NET formation by direct action on neutrophils (14). The treatment was administered with an Aerogen® Solo in-line nebulizer to avoid open aerosol generation, which would place staff at risk of exposure to SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%
“…All patients received the same treatment doses: nebulized dornase alfa (2.5 mg) co-administered twice daily with the short-acting β 2 -agonist albuterol (2.5 mg, hereafter abbreviated as nDA+A) to improve delivery to the alveoli. Of note, β 2 -adrenoreceptor agonism may also inhibit NET formation by direct action on neutrophils (14). The treatment was administered with an Aerogen® Solo in-line nebulizer to avoid open aerosol generation, which would place staff at risk of exposure to SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies showed that neutrophils express both αARs and βARs including α 1A , α 2C , α 1D , β 1 , β 2 , and β 3 ARs but not α 2B ARs mRNA [52,[58][59][60][61][62][63]. The expression of αARs in neutrophils has been confirmed in multiple studies related to diverse physiological conditions [52,61].…”
Section: Catecholamines and Their Effects In Neutrophilsmentioning
confidence: 86%
“…βARs are predominantly anti-inflammatory. in vitro studies showed that βARs modulate neutrophil oxidative burst, chemotaxis, NET formation, and the expression of adhesion molecules, leukotriene B 4 (LTB 4 ), and chemokines/cytokines [62][63][64][65]. The intracellular βAR signaling, especially those associated with cAMP and PKA activation, modulate most to the neutrophil functions [66,67].…”
Section: Catecholamines and Their Effects In Neutrophilsmentioning
confidence: 99%
“…PMN migration was investigated by the Boyden chamber assay modified as previously described [46]. Briefly, after instrument assembly, PMN at 1 × 10 6 cells/mL in RPMI 1640 medium were placed in the upper chamber alone or together with the test substance, while the lower chamber contained medium alone (spontaneous migration) or added with 10 ng/mL interleukin (IL)-8 (Sigma–Aldrich, code: I1645) or 0.1 μM N-formyl-Met-Leu-Phe (fMLP, Sigma–Aldrich, code: F3506) (stimulated migration).…”
Section: Methodsmentioning
confidence: 99%